Dilapidated to vibrant: adaptive reuse as a catalyst for regenerating urban areas through public private partnerships - Pileggi, John Robert (Kansas State University, 2024)
Adaptive reuse has risen as a key strategy in rejuvenating urban spaces, particularly in response to the post-World War II shift towards suburbanization which left many city centers with unused industrial buildings. This approach reimagines these structures not as obsolete remnants, but as valuable assets for urban renewal. The role of public-private partnerships (PPPs) in this context has been pivotal, merging the preservation of historical heritage with meeting modern urban needs. In this report, the potential of adaptive reuse, backed by PPPs, to transform urban landscapes into vibrant, sustainable areas is thoroughly examined. The research includes an extensive review of relevant literature and a comparative analysis. It focuses on three distinct case studies: The West Bottoms and The Crossroads Arts District in Kansas City, Missouri, and The Old Market in Omaha, Nebraska, each selected for their unique contributions to the practice of adaptive reuse. Interviews with experts in urban planning, development, and economic development enrich the study with diverse perspectives and in-depth knowledge. The findings from these cases provide a comprehensive view of the adaptive reuse process, encompassing various stages from planning to implementation, and involving a range of professionals and organizations. The report culminates in a detailed synthesis of adaptive reuse principles, highlighting its vital role in fostering dynamic, sustainable, and culturally vibrant urban environments.
Keywords: Adaptive reuse; Public private partnerships